2004
DOI: 10.1021/jf034871e
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Quantitation of Genetically Modified Maize (Bt-176 Transgenic Maize) by Applying Ligation Detection Reaction and Universal Array Technology

Abstract: We have applied the ligation detection reaction (LDR) combined with a universal array approach to the detection and quantitation of the polymerase chain reaction (PCR) amplified cry1A(b) gene from Bt-176 transgenic maize. We demonstrated excellent specificity and high sensitivity. Down to 0.5 fmol (nearly 60 pg) of PCR amplified transgenic material was unequivocally detected with excellent linearity within the 0.1-2.0% range with respect to wild-type maize. We suggest the feasibility of extending the LDR/unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 12 publications
0
18
0
1
Order By: Relevance
“…In comparison to other array-based GMO detection methods, the method presented in this study shows comparable performances in terms of specificity and relative sensitivity; most other methods being able to detect as low as 0.1% GM contents (6,9,29,31), and some being slightly less sensitive (8,10). The absolute sensitivity of the NAIMA amplification method combined with microarray detection (∼60 pg) is also favourable when compared to the above-cited methods, since several methods require starting amounts of DNA from 10 to 500 ng (8,10,31), two methods requiring 60 pg (29) and 300 pg (6).…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…In comparison to other array-based GMO detection methods, the method presented in this study shows comparable performances in terms of specificity and relative sensitivity; most other methods being able to detect as low as 0.1% GM contents (6,9,29,31), and some being slightly less sensitive (8,10). The absolute sensitivity of the NAIMA amplification method combined with microarray detection (∼60 pg) is also favourable when compared to the above-cited methods, since several methods require starting amounts of DNA from 10 to 500 ng (8,10,31), two methods requiring 60 pg (29) and 300 pg (6).…”
Section: Resultsmentioning
confidence: 81%
“…Regarding the performance, NAIMA amplification shows very fast kinetics that are comparable with the fastest qPCR systems currently available, as the duration of a qPCR amplification run varies from 30 min to 2 h (28). NAIMA is also generally a faster amplification method when compared to other multiplex amplification methods combined with microarray detection applied to GMO diagnostics (6–10,12,29). Most of the qPCR methods validated by the CRL for GMO detection include cycles of 75 s, for which a maximum of 7·10 10 -fold amplification rate (for 36 cycles) is possible in 45 min at 100% reaction efficiency (http://gmo-crl.jrc.it/statusofdoss.htm).…”
Section: Resultsmentioning
confidence: 99%
“…Bordoni et al (2004) reported a sensitivity of 0.1% for the Bt176 transgenic maize and can identify the presence of 0.5% transgenic events within complex mixtures of RRS, Bt11, MON810, GA21 and Bt176 (Bordoni et al, 2005). Recently, a peptide nucleic acid (PNA) array platform was reported for the detection of GMO in food: in this paper , PNA array showed a high selectivity for several 5% GM events and two specific plant genes (lectin for soybean and zein for maize).…”
Section: Discussionmentioning
confidence: 99%
“…Different DNA microarray approaches have been developed to be used in combination with multiplex PCRs: a multiplex DNA array-based PCR allowing quantification of transgenic maize in food and feed (Rudi et al, 2003); a ligation detection reaction coupled with an universal array technology allows the detection of the Bt176 transgenic maize (Bordoni et al, 2004) or five transgenic events (Bordoni et al, 2005); and recently, a peptide nucleic acid array approach was developed for the detection of five transgenic events and two plant species . These methods used fluorescent probes, which require costly material and are photosensitive, thus limiting the common use of microarrays for GM detection.…”
Section: Introductionmentioning
confidence: 99%
“…12 The ligation detection reaction was combined with a universal array approach to detect and quantitate the PCR-amplified Cry1A(b) gene from BT-176 transgenic maize with excellent specificity and high sensitivity. 13 An immono-PCR based method showed minimum detection limit 21.6-436 ng to detect insecticidal protein Cry1Ac toxin, produced by Bacillus thuringiensis. 14 In a need to apply a screening method that is sensitive and unambiguous in identifying the different transformation events, a small amount of DNA required by TAIL-PCR was easily recovered from small transformant that allows rapid verification of T-DNA integration and detection of separate gene transfer event.…”
Section: Tracking Of Genetically Engineered Dna In the Environmentmentioning
confidence: 99%